Four Decades of Health Economics through a Bibliometric Lens - Wagstaff, Adam; Culyer, Anthony J. (2012)
This paper takes a bibliometric tour of the past 40 years of health economics using bibliographic "metadata" from EconLit supplemented by citation data from Google Scholar and the authors' topical classifications. The authors report the growth of health economics (33,000 publications since 1969 -- 12,000 more than in the economics of education) and list the 300 most-cited publications broken down by topic. They report the changing topical and geographic focus of health economics (the topics 'Determinants of health and ill-health' and 'Health statistics and econometrics' both show an upward trend, and the field has expanded appreciably into the developing world). They also compare authors, countries, institutions, and journals in terms of the volume of publications and their influence as measured through various citation-based indices (Grossman, the US, Harvard and the JHE emerge close to or at the top on a variety of measures).